Flexural strength and failure behavior of glass laminate aluminum reinforced epoxy and aluminum-lithium laminates in abrasive water jet peening under contamination - Qutaba, Syed; Sandy, Galang; Ahmed, Sajjad; Azmir, Azhari (Universiti Malaysia Pahang, 2025)
Abrasive Waterjet Peening (AWJP) technology has been widely utilized for various machining, surface treatment, and material indentation applications. The goal of this study is to investigate the influence of AWJP parameters (stand-off distance, water pressure, abrasive size, and number of passes) on the bending strength and types of damage during the peening process of the Fiber Metal Laminates (FML). The surface treatment with AWJP has resulted in variant effects on the surface of the FML. Furthermore, the effect of FML structure with spreading layers was investigated for deformation during the AWJP process. Analysis of variance (ANOVA) was used in the present study to evaluate the effect of AWJP parameters on the failure behavior of 3/2 aluminum-lithium alloy and glass fiber laminate. Results indicated that the fiber layers hindered the deformation of the aluminum-lithium layer. Moreover, the layup of fiber layers and the abrasive size affected the craters’ shape on the metallic surface of aluminum-lithium layers. In terms of four parameters, it was found that the medium level of parameters was sufficient based on ANOVA, which showed a higher flexural strength (up to 482 MPa). Based on the results related to flexural strength, the residual stress field of the FMLs under multiple passes indentation was simulated as the higher flexural strength. The prediction and actual values were consistent with the experimental results, with the overall increase being ± 10%. “Effect” A morphology study revealed that “FML flexural strength deteriorated and caused damage due to the high impact intensity of peening with increases in the craters effect.” Hence, resistance is effective at low impact due to the high craters effect.